2022
DOI: 10.1186/s13027-022-00427-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathogens and prostate cancer

Abstract: Background The aim of this review is to consider whether multiple pathogens have roles in prostate cancer. Methods We have reviewed case control studies in which infectious pathogens in prostate cancer were compared to normal and benign prostate tissues. We also reviewed additional evidence from relevant published articles. Results We confirmed that high risk human papilloma viruses are a probable caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 141 publications
(114 reference statements)
0
14
0
1
Order By: Relevance
“…For instance, when examining the pathways enriched in EBV-positive and -negative PCa tissues, we observed that the pathway leading to the control of herpes virus infection was enriched, and the studied miRNAs were downregulated, suggesting poor control of herpes infection and enhanced progression of prostate cancers. This finding is particularly significant given previous research demonstrating a connection between herpesviruses and the development of PCa 110 , 111 .…”
Section: Discussionmentioning
confidence: 51%
“…For instance, when examining the pathways enriched in EBV-positive and -negative PCa tissues, we observed that the pathway leading to the control of herpes virus infection was enriched, and the studied miRNAs were downregulated, suggesting poor control of herpes infection and enhanced progression of prostate cancers. This finding is particularly significant given previous research demonstrating a connection between herpesviruses and the development of PCa 110 , 111 .…”
Section: Discussionmentioning
confidence: 51%
“…However, microbial pathogens such as bacteria and viruses are implicated in cancers of the prostate and cervix. Approximately 20% of cancer incidences are caused by infectious agents, and a good number of studies have shown the presence of some bacterial and viral agents such as Escherichia coli , Cutibacterium acnes , Neisseria gonorrhea , HPV, Herpes simplex , Epstein–Barr virus, and Mycoplasmas [ 28 , 29 ]. Lawson et al (2022) concluded in their pooled studies that, except for HPV, the microorganisms mentioned earlier have roles in PCa oncogenesis, which is yet to be proven.…”
Section: Microbial Agents and Cancermentioning
confidence: 99%
“…In addition to bacteria, viruses may also contribute to prostate cancer development. For instance, HPV can immortalize normal human PECs, and there is strong evidence supporting the association of HPV infection with increased risk of prostate cancer [125][126][127]. Other viruses, such as CMV or Polyoma viruses, may also play a role in prostate cancer, but the association is not significant [126].…”
Section: Microbes In Prostate Tissue and Cancermentioning
confidence: 99%